Implementasi Quality of Service pada Protokol Message Queue Telemetry Transport - Sensor Network (MQTT-SN) Berbasis Arduino dan NRF24L01 - Sofi Hanifah; Sabriansyah Rizqika Akbar; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Message Queue Telemetry Transport - Sensor Network (MQTT-SN) is a communication protocol derived from the Message Queuing Telemetry Transport (MQTT) protocol that applied to the sensor network. To apply MQTT-SN requires Quality of Service (QoS). QoS is a method of measuring the quality of network and an attempt to define the characteristics and properties of a service so that messages are received. The Application of QoS in MQTT-SN is very important to ensure the receipt of data. This research implies QoS mechanism on Arduino Nano with NRF24L01 wireless communication using MQTT-SN message format. In this research is tested with different QoS level to get different result in each level of QoS. MQTT-SN with QoS level 0 allows packets not to reach the gateway because publishers continue to publish without any reciprocity from the gateway that make publishers don't know wether the message is delivered to the destination or not, and average accepted message 70%. While MQTT-SN with QOS level 1 the gateway can not distinguish publish data at the first time and next so duplicated messages can be happen until 30%. MQTT-SN with QoS level 2, the message is received exactly once due to temporary data storage on the gateway that make protocol will ignore data that is not needed and average accepted message 100%.